1600 Shifting times: recent rotational shiftwork and incident hypertension risk. (24th April 2018) - Ferguson, J; Costello, S; Cullen, M; Eisen, E
Abstract : Introduction: Rotational shiftwork, such as alternating day, afternoon, and night shifts, causes chronobiologic phase disruptions which may cause an increase in hypertension risk. Prior research has classified rotational shiftwork using assigned schedules in lieu of actual recorded work which may result in exposure misclassification. Therefore, we assessed the association between a novel quantitative definition of rotational shiftwork and incident hypertension. Methods: A cohort of 2156 new hires at 9 aluminium smelter and fabrication facilities were followed from 2003 through 2013 for incident hypertension defined by ICD-9 codes from insurance claims. Detailed time-registry data was used to classify each worker's history of rotational shiftwork. Rotational shiftwork was defined as shift with a larger than 4 hour absolute value change in start time from the preceding shift that started on an earlier day. The association between incident hypertension and rotational shiftwork in the previous 12 months was estimated in a Cox proportional hazards model, adjusting for age, sex, facility, smoking history, annual BMI, annual health claims based risk score, night shift exposure (percentage of shifts that were night shifts cumulatively and in the previous year), and history of rotational work. Results: The majority of workers (99.8%) experienced at least one rotation in their work history. The average worker had at 2.91 rotations (SD=1.87) per month with a mean of 130 rotations over their work history. Compared with workers with less than 5% rotational shiftwork in the previous year, the hazard ratio among workers with ≥5-<15%, ≥15-<30%, and ≥30% rotational shiftwork in the previous year were 1.02 (0.64–1.64), 1.13 (0.73–1.76), and 1.53 (0.95–2.45) respectively. Estimates were robust to the adjustment for night shifts Conclusion: Our results suggest recent rotational shiftwork exposure may be associated with higher rates of hypertension. Furthermore, rotational shiftwork may have an independent effect on hypertension risk not explained by night work.